Cover Picture: The Energy Landscape of Uranyl–Peroxide Species (Chem. Eur. J. 13/2014). Issue 13 (24th March 2014) - Tiferet, Eitan; Gil, Adrià; Bo, Carles; Shvareva, Tatiana; Nyman, May; Navrotsky, Alexandra
<x xml:space="preserve">Abstract</x> Weighing in…︁ on uranyl phase stability. Two uranyl polyoxometalates that differ only by the anion encapsulated in the center are assessed by computational and experimental methods. Thermodynamic and molecular‐orbital calculations agree that stability is gained by increasing cation/anion interactions. This agrees with the trend of all uranyl phases that range in dimension from monomers to infinite solids. For more information, see the Full Paper by M. Nyman, A. Navrotsky et al. on page 3646 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>